COMPUTATION OF NATURAL CONVECTION IN A POROUS PARALLELOGRAMMIC ENCLOSURE WITH A MAGNETIC FIELD - Saleh, Habibis; Basriati, Sri; Hashim, Ishak (Makara Journal of Science, 2010)
Detailed numerical calculations are presented in this paper for natural convection in a porous parallelogrammic enclosure with a magnetic field. The inclined walls are maintained isothermally at different temperatures. The top and bottom horizontal straight walls are kept adiabatic. To simplify the effort in matching the grid mesh with the inclined walls of the parallelogrammic region/geometry, the computational domain is mapped onto a rectangular shape using a non-linear axis transformation. Transport equations are modeled by a stream-vorticity formulation then expressed in the new coordinate system and solved numerically by a finite difference method. Based upon the numerical predictions, we found the convection modes within the enclosure depended upon the Rayleigh number and the inclination angle. As the value of magnetic field is made larger, the strength of the heat transfer is progressively suppressed. Tuning the inclination angle decreases the heat transfer performance.